CHARACTER REVITALIZATION THROUGH ISLAMIC RELIGIOUS EDUCATION IN SMPN 1 MANDAILING NATAL: Revitalisasi Karakter Melalui Pendidikan Agama Islam di SMPN 1 Mandailing Natal - Kholidah Nur; Ali Masran Daulay; Junita Irawati (STAI Ma'had Aly Al-Hikam Malang, 2025)
diversity makes it a nation that has its own character that is different from other nations. This character should be maintained through educational institutions in order to produce a generation of the nation that knows and preserves the character of the nation that has existed since their ancestors. This study uses a qualitative approach with a post-positivistic paradigm. Data collection through interviews, observations, and documentation. While data analysis with the Miles, Huberman & Saldana model. This study resulted in a shift in the character of the Indonesian nation that is classified as very complicated, this complexity is further complicated by the lack of public awareness that our national character has long been lost. The glittering currents of modernization and globalization are the main factors in the loss of the nation's character. The readiness of society to face the modern era forces them to fall asleep and be lulled by the strains of electronic sophistication without being able to fortify themselves with sufficient knowledge. Likewise, the sudden flow of globalization cannot be blocked by clarity of heart and mind so that it blinds the paradigm of long-term thinking. As a result, the character of the nation is now just a sweet memory when remembered and bitter when remembered. The development of national character in schools through Islamic religious education is carried out in several stages, namely familiarizing oneself with religious activities, action planning and giving awards. Bangsa Indonesia adalah bangsa yang memiliki bermacam ras budaya yang bermacam-macam. Keanekaragaman ini menjadikannya sebagai bangsa yang memiliki karakter sendiri berbeda dengan bangsa yang lain. Sekolah sebagai lembaga pendidikan formal harusnya mampu menjadi benteng dalam internalisasi karakter bangsa ini ke dalam diri peserta didik sehingga melahirkan peserta didik yang berkarakter. Penelitian ini menggunakan pendekatan kualitatif dengan paradigma post positivistik. Lokasi penelitian ini di SMPN 1 Mandailing Natal. Pengumpulan data dengan wawancara, observasi, dan dokumentasi. Sementara analisis data dengan model Miles, Huberman & Saldana. Penelitian ini menghasilkan pergeseran karakter bangsa Indonesia tergolong sangat rumit, kerumitan ini dipersulit lagi dengan kurangnya kesadaran mayarakat bahwa karakter bangsa kita sudah lama hilang. Gemerlapnya arus modernisasi dan globalisasi menjadi faktor utama hilangan karakter bangsa tersbut. Kesiapan masyarakat menghadapi zaman modern memaksa mereka untuk larut tertidur dan dibuai manja oleh alunan kecanggihan elektronik tanpa mampu membentengi diri dengan pengetahuan yang cukup memadai. Demikian halnya dengan arus globalisasi yang serba dadakan tidak mampu dibendung dengan kejernihan hati dan pikiran, sehingga membutakan paradigma berpikir panjang. Akibatnya, karakter bangsa kini tinggal kenangan manis bila ingat dan pahit bila kenang. Pembangunan karakter bangsa di sekolah melalui pendidikan agama Islam dilakukan dengan beberapa tahapan, yaitu pembiasaan kegiatan keagamaan, perencanaan aksi dan pemberian penghargaan. Key Words : Character; Islamic Religious Education; Revitalization; School.